2017
DOI: 10.1590/1980-5918.030.003.ao04
|View full text |Cite
|
Sign up to set email alerts
|

Test timed up and go and its correlation with age and functional exercise capacity in asymptomatic women

Abstract: Introduction:The Timed Up and Go test (TUG) is widely used and valid in chronic patients, but rarely addressed in asymptomatic individuals. Objective: To assess the reliability, the age-related changes and the correlation between TUG and the Functional Exercise Capacity (FEC) adjusted for non-institutionalized middle-aged and elderly women. Methods: Ninety-eight women (57 ± 10 years) were selected and stratified into age groups. We have performed the tests TUG, Berg Balance Scale (BBS) and evaluation of usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…This finding aligns with previous reports confirming the link between age and TUG performance [ 31 , 33 , 34 ]. A study on 98 women found similar worse performance in TUG for those aged ≥70 years and 40–59 years [ 36 ]. The worst performance on the TUG in women could be due to decreased mobility [ 37 ] and weakness in lower limb muscles, particularly in the older adult group [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with previous reports confirming the link between age and TUG performance [ 31 , 33 , 34 ]. A study on 98 women found similar worse performance in TUG for those aged ≥70 years and 40–59 years [ 36 ]. The worst performance on the TUG in women could be due to decreased mobility [ 37 ] and weakness in lower limb muscles, particularly in the older adult group [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…), it is already of great importance. utility, if not enough, the evaluative/predictive power to measure possible decline in body balance among the elderly (36,38,40) -inferring, based on these primary findings, something about the power/ duty to act early in the case of the elderly, avoiding the need for interventions at more specialized and expensive levels of care (46).…”
Section: Other Relevant Discussionmentioning
confidence: 99%
“…In this Integrative Review, it was found that the application of the Berg Scale was varied, however, there was a predominance of execution in the community (18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,33,34,35,36,37,38,39,40,41,42), coexistence center (18,19,31,34), school clinic of Physical Therapy in the community (20,24,29,30,33), Primary Health Care.…”
Section: Berg-bse Balance Scale;mentioning
confidence: 98%
“…The TUG was measured to determine agility, dynamic balance and capacity of autonomous movement. When signalled to do so, the subject got up and moved as soon as possible to a line situated at a distance of 3 m and returned to the starting position, covering a total of 6 m [22]. The fastest result out of two was noted.…”
Section: Methodsmentioning
confidence: 99%